The complete mitochondrial genome of the 'solar-powered' sea slug Plakobranchus cf. ocellatus (Heterobranchia: Panpulmonata: Sacoglossa). Issue 1 (1st January 2017) - Greve, Carola; Ruiz-Tagle Lui, Maximiliano; Sivalingam, Sugirthan; Ludwig, Kerstin U.; Wägele, Heike; Donath, Alexander
Abstract: We present the complete mitochondrial genome sequence of Plakobranchus cf. ocellatus (Heterobranchia: Sacoglossa), a so-called 'solar-powered' sea slug with long-term retention of chloroplasts. The mitochondrial genome was 14, 177 bp in length containing the standard set of 13 protein-coding genes, 2 rRNAs, and 22 tRNAs. The base composition of 27.3% A, 15.6% C, 18.6% G, and 38.5% T showed a strong A + T bias. The genome organization of P. cf. ocellatus is identical to the other sacoglossan mitogenomes sequenced so far, except for Ascobulla fragilis .